Pengaruh Upah Minimum, Jumlah Penduduk, dan Inflasi Terhadap Tingkat Pengangguran di Kabupaten Kupang - Onta, Damasius; Ballo, Fransina W.; Kiak, Novi Theresia (RJABM (Research Journal of Accounting and Business Management), 2023)
This research aims to explain the influence of the minimum wage, population and inflation on the unemployment rate in Kupang Regency. This research is quantitative research with time series data for 19 years, namely in the observation period 2004-2022. The data used are minimum wage growth rate data, population growth rate data and inflation rate data sourced from the Kupang Regency Central Statistics Agency. The analytical method used is multiple linear regression analysis which is processed using Eviews-12 software. The results of this research show that partially the minimum wage variable has a positive relationship and hasa significant effect onthe unemployment ratein Kupang Regency. Meanwhile, the population variable and the inflation variable do not have a significant effect on the unemployment rate in Kupang Regency. Simultaneously, the variables minimum wage, population and inflation have a significant effect on the unemployment rate in Kupang Regency.